Maternal, Obstetric, and Infant Factors and Their Associatio with the Risk of HIV Infection in Infants at Dr. Moewardi Hospital, Surakarta - Rahmawati, Deni Nur Fauzia; Respati, Supriyadi Hari; Hanim, Diffah (Journal of Maternal and Child Health, 2016)
Background: Incidence of HIV infection by mother to child transmission has been increasing for the past few years. This study aimed to determine the association between maternal, obstetric, infant factors, and the risk of HIV infection in infant.Subjects and Method: This was an analytic observational study using case control design. This study was conducted at Dr. Moewardi Hospital, Surakarta. A total of 68 study subjects, consisting of 34 HIV infected infants, and 34 non HIV infected infants, were selected for this study by fixed disease sampling. The dependent variable was HIV infection. The independent variable included maternal nutrirional status, opportunistic infection, antenatal care, type of labor, birth weight, and prematurity. The data were collected by a set of questionnaire and analyzed using logistic regression model.Results: Maternal HIV opportunistic infection (OR= 10.09; 95% CI= 1.99 to 51.20; p=0.005) and pervaginam labor (OR=5.21; 95% CI=0.92 to 29.58; p=0.063) increase the risk of HIV infection in infant, and they were statistically significant. Maternal body weight (BMI<18.5)(OR=2.71; 95% CI=0.44 to 16.53; p=0.280), antenatal care <4 times (OR=1.94; 95% CI= 0.42 to 9.00; p=0.395), birth weight <2.500 gram (OR=1.09; 95%CI=0.19 to 6.05;p=0.924) and prematurity (OR= 1.65; 95% CI=0.36 to 7.61; p=0.523), each increased the risk of HIV infection but statistically non-significant.Conclusion: Maternal HIV opportunistic infection and pervaginam labor are strong and significant predictors for the risk of infant HIV infection. Health personnel should pay special attention on these significant risk factors when assisting birth delivery, in order to prevent HIV infection in infants.Keywords: maternal, obstetric, infant risk factors, HIV infection.Correspondences:ÃÂ Deni Nur Fauzia Rahmawati. Masters of PublicÃÂ  Health Program, Sebelas Maret University. Email: denierahmawati@gmail.comJournal MaternalÃÂ  and Child Health (2016), 1(2): 73-82https://doi.org/10.26911/thejmch.2016.01.02.02